Phytochemical screening and evaluation of analgesic and antiinflammatory activities of Phaseolus vulgaris linn., seeds in rodents - M. R. Pradeepkumar, Shrinivas D. Joshi, V. H. Kulkarni, Chetan Savant (Journal of Applied Pharmaceutical Science, 2015)
With an objective of developing some novel analgesic and antiinflammatory natural agents with fast acting and low toxicity profile herein, the different extracts of Phaseolus vulgaris (Linn) seeds were evaluated for analgesic and antiinflammatory activities using glacial acetic acid induced writhing and carrageenan induced rat paw oedema method respectively. For screening of the extracts for analgesic and antiinflammatory activities aspirin and diclofenac were used as standard drugs respectively. Petroleum ether extract exhibited significant analgesic and antiinflammatory activities. The petroleum ether extract can be considered as a potential candidate for analgesic and antiinflammatory activities. The presence of steroids and flavonoids in petroleum ether extract of Phaseolus vulgaris Linn., seeds could be attributed for the analgesic and antiinflammatory activities.
Keywords: Analgesic, Antiinflammatory, Phaseolus vulgaris Linn., seeds, carrageenan, glacial acetic acid.